Palhaço no hospital: percepção da influência do pronto sorriso como instrumento de aprendizagem no ensino da graduação em medicina - Oliveira, Arlene de Sousa Barcelos (2014)
“Pronto Sorriso” is an open core course of the medical school at Federal University of Goias, with the mission of holistic training of academics through entertainment and performing arts, prompting the creation of the hospital clown, and other recreational activities. Objective: To analyze the influence of “Pronto Sorriso” as a tool for humanistic training of academic medicine in the hospital environment. Materials and Methods: A qualitative, exploratory, cross imprint study involving graduate students of the Faculty of Medicine of the Federal University of Goias who participated in “Pronto Sorriso” in 2012/2013. Data were collected through recorded interviews, using a questionnaire as a tool and a roadmap for a semi-structured interview, which was conducted with the participants of the course and healthcare professionals of the university hospital, seeking to identify the perceived influence of “Pronto Sorriso” in academic training. To analyze results, Bardin’s content analysis technique was used. Results: The sample consisted of 30 participants, 20 being medical students, and ten health professionals in a pediatric unit of Hospital das Clinicas of UFG, who signed the consent form. The average age of students was 19 years, with a predominance of single and female. For healthcare professionals, the average age was 42 years and with over 10 years experience in the research institution. We chose to analyze the interviews in two separate groups: interviews of medical students and interviews with health professionals active in the pediatric unit of the teaching hospital. Conclusion: The study concludes that “Pronto Sorriso” is an instrument of humor providing humanistic training in medicine as well as transformation of the hospital, and provides knowledge and development of skills related to medical clowns.